Budidaya Tanaman Sayuran dan Tanaman Obat Keluarga di Pekarangan Berbasis Pertanian Ramah Lingkungan di Kecamatan Sariwangi - Yuni Ertinawati; Selly Purnama; Shinta Rosiana; Ida Wahidah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The potential of agricultural resources is one of the great potentials possessed by Tasikmalaya Regency, especially Sariwangi District. Management of yard land by utilizing the role of women can be a solution in optimizing yard land to increase food yields. The objectives of the activity "Cultivation of Family Vegetables and Medicinal Plants in the Garden-Based on Environmentally Friendly Agriculture in Sariwangi District" are: 1) Cultivating family vegetables and medicinal plants, 2) Increasing the active role of women, especially members of women farmer groups in optimizing yard land, 3) With the selection of environmentally friendly-based agriculture, namely as an alternative to the production of healthy food. This system cultivates plants by minimizing the use of chemicals, which in the future will ensure the sustainability of farming. The implementation of Community Service for the Food Security Scheme was carried out in the Srikandi Tani Women Farmer Group (KWT) in Peundeuy Village, Sukaharja Village, Sariwangi District, and the Sukariksa III Farmer Women's Group (KWT) Benjan Village, Sukamulih Village, Sariwangi District. The methods of implementing this PbM-KP activity are: a) Conducting interviews with members of the Women Farmers Group (KWT) Srikandi Tani and Sukariksa III, b) Counseling and practice activities regarding the cultivation of vegetables and family-based medicinal plants that are environmentally friendly c) Evaluation to find out how much great success of the implementation of these activities. The evaluation results show that on average the KWTs have played an active role in optimizing their yards through the cultivation of family vegetables and medicinal plants. Several types of vegetables have been able to enjoy the results.